Halal Life Style: Pengaruh Labelitas Halal Dan Harga Makanan Olahan Impor Terhadap Keputusan Pembelian Masyarakat Di Kota Metro - El Maza, Rina; Suri Rismawati, Dian; Imtihanah, Ani Nurul; Nazeri, Nazeri (Universitas Muhammadiyah Ponorogo, 2024)
Food is a basic human need. A person is given complete freedom to consume whatever they need. However, when making purchasing decisions, a Muslim is not permitted to consume food that is not halal (haram). It is feared that the rise of imported processed food circulating in Indonesia will trigger Muslim communities to buy processed food not based on the halal label but only considering the price of the product. This type of research is field research using quantitative methods. The technique used in sampling in this research is Non Probability. The number of samples used was 100 respondents, namely the Muslim community in Metro City. With multiple regression analysis using SPSS version 23 which functions to prove the research hypothesis. The results of this research show that the halal label variable has a partial and significant effect on purchasing decisions and the price variable has a partial and significant positive effect on purchasing decisions. Then, through the F test, the halal label and price simultaneously influence the decision to purchase imported processed food products. This effect is explained by the large significant level of the halal label and the price of 0.000 which is less than 0.1 or tcount>ttable (21.752) > (2.36